2010
DOI: 10.5004/dwt.2010.1054
|View full text |Cite
|
Sign up to set email alerts
|

The fate of transparent exopolymer particles (TEP) in seawater UF-RO system: A pilot plant study in Zeeland, The Netherlands

Abstract: A B S T R A C TFor many years, transparent exopolymer particles (TEP) were found abundant in various marine and freshwater environments, which are currently the main sources of raw water in desalination plants. Just recently, TEP have been identified as a potential foulant capable of causing organic and biological fouling in membrane systems. A pilot plant study was conducted to monitor the fate of TEP through the treatment process and to investigate their effects on the operational performance of a seawater U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…However, some concerns have been expressed regarding the rate of fouling in UF membrane systems (e.g. backwashable and nonbackwashable fouling) during algal bloom period [59][60][61][62]. To overcome this concern, incorporating in-line coagulation or a DAF system preceding a UF system has been recommended [63].…”
Section: Impact Of Algal Blooms On Swro Operationmentioning
confidence: 99%
“…However, some concerns have been expressed regarding the rate of fouling in UF membrane systems (e.g. backwashable and nonbackwashable fouling) during algal bloom period [59][60][61][62]. To overcome this concern, incorporating in-line coagulation or a DAF system preceding a UF system has been recommended [63].…”
Section: Impact Of Algal Blooms On Swro Operationmentioning
confidence: 99%
“…We suggest much of the TEP in the DCM was formed from abiotic self-assembly of smaller precursors (Verdugo & Santschi 2010). Because we measured only the concentrations of TEP retained on 0.4 µm filters (see 'Materials and methods'), we were unable to determine the concentrations of any precursor pool of smaller (0.05 to 0.4 µm), colloidal-sized TEP (Villacorte et al 2010) that may have been significant at these depths.…”
Section: Depth Distribution Of Tep: Particle Formation Utilization mentioning
confidence: 99%
“…Therefore, the removal of TEP from feedwater reaching filtration membranes and other sensitive surfaces is now recognized as an effective means of inhibiting biofilm development. However, some studies have shown that current pretreatment technologies are not very efficient at lowering TEP concentrations in feedwater [25], most likely because of the amorphous, deformable, microgel nature of these particles [10,26]. For example, Bar Zeev et al [17] found that although pretreatment at an operational desalination plant lowered the levels of water quality parameters such as Chl and SDI by $90% relative to input, TEP concentrations were only decreased by $30% upstream of the RO membranes.…”
Section: Amf Filtration Efficiencymentioning
confidence: 95%